1988
DOI: 10.1159/000284541
|View full text |Cite
|
Sign up to set email alerts
|

Panic Attacks with and without Agoraphobia: a Comparison

Abstract: 22 patients with panic disorder (PD) were compared with 42 cases suffering from agoraphobia with panic attacks for a number of variables. The two groups did not differ for age, sex ratio, age of onset, social class, severity of nonsituational anxiety and personality profiles. On the other hand agoraphobics showed lower education and worse social adaptation. A higher prevalence of traumatic life events was also observed for agoraphobics compared with subjects suffering from PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…These results are in line with the findings of most authors [16][17][18]33] and confirm the changes of DSM-III-R [2], The trend of a female preponderance in panic patients with avoidance behavior compared to panic pa tients without avoidance behavior corre sponds with many other studies [ 10. 12],…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in line with the findings of most authors [16][17][18]33] and confirm the changes of DSM-III-R [2], The trend of a female preponderance in panic patients with avoidance behavior compared to panic pa tients without avoidance behavior corre sponds with many other studies [ 10. 12],…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the present data indicate that panic disorder and avoid ance behavior occur tightly linked in time in many panic disorder patients with agorapho bia. The finding of almost identical mean ages at onset of panic disorder and avoidance be havior in a considerable number of patients challenges the suggestion that phobic avoid ance behavior usually is secondary to recur rent panic attacks [7] and supports the view of other authors that avoidance behavior is not only a secondary complication of panic at tacks [10,11,16,33], Three heterogeneous subgroups were dis criminated by means of analysis of the symp tom onset sequences of panic disorder and avoidance behavior according to Aronson and Logue [12], Craske and Barlow [24], and Lelliott ct al. [25].…”
Section: Discussionsupporting
confidence: 51%
“…[ 10 , 34 ] Few studies have compared MMPI in panic disorder patients with and without agoraphobia. One study revealed that PDA patients’ psychasthenia score was higher than those with PD, [ 35 ] which is consistent with the current findings. Overall, patients with PDA are prone to more affective symptoms compared to patients with PD.…”
Section: Discussionsupporting
confidence: 92%
“…This study must therefore be viewed as a step to approximate the construct of the role of early experiences for panic and agoraphobia rather than as a conclusive one. This study is part of a broader project aimed at exploring the childhood experiences of panic patients by integrating the evaluation of: 1) the subjectively perceived climate of childhood (by the PBI); 2) the objective recall of early life events (already published in part (29,30); 3 ) the actual evaluation of the parental attitudes of the mothers of these patients by means of the Parental Attitudes Research Instrument (31); and 4) the prevalence of anxious and depressive pathology among parents.…”
Section: Discussionmentioning
confidence: 99%